Can we safely recommend gestational weight gain below the 2009 guidelines in obese women? A systematic review and meta‐analysis. Issue 3 (18th January 2015) - Kapadia, M. Z.; Park, C. K.; Beyene, J.; Giglia, L.; Maxwell, C.; McDonald, S. D.
Summary A systematic review was conducted to determine the risk of adverse pregnancy outcomes with gestational weight gain (GWG) below the 2009 Institute of Medicine guidelines compared with within the guidelines in obese women. MEDLINE, Embase, Cochrane Register, CINHAL and Web of Science were searched from 1 January 2009 to 31 July 2014. Quality was assessed using a modified Newcastle–Ottawa scale. Three primary outcomes were included: preterm birth, small for gestational age (SGA) and large for gestational age (LGA). Eighteen cohort studies were included. GWG below the guidelines had higher odds of preterm birth (adjusted odds ratio [AOR] 1.46; 95% confidence interval [CI] 1.07–2.00) and SGA (AOR 1.24; 95% CI 1.13–1.36) and lower odds of LGA (AOR 0.77; 95% CI 0.73–0.81) than GWG within the guidelines. Across the three obesity classes, the odds of SGA and LGA did not show any notable gradient and remained unexplored for preterm birth. Decreased odds were noted for macrosomia (AOR 0.64; 95% CI 0.54–0.77), gestational hypertension (AOR, 0.70; 95% CI 0.53–0.93), pre‐eclampsia (AOR 0.90; 95% CI 0.82–0.99) and caesarean (AOR 0.87; 95% CI 0.82–0.92). GWG below the guidelines cannot be routinely recommended but might occasionally be individualized for certain women, with caution, taking into account other known risk factors.